Generality Analysis Method of Research Papers Using User Behavior Data on the Internet - YOSHIDA, Mitsuo; SATO, Sho; KOBAYASHI, Kazuhisa; OHMUKAI, Ikki; KAZAMA, Kazuhiro (Joho Chishiki Gakkaishi, 2020)
As an evaluation index of academic papers, the citation count of papers has conventionally been used,but in recent years, a method that uses reactions on social media such as altmetrics has been proposed. In this paper, we propose a method to analyze the characteristics of a paper using a general degree that indicates how generally read, in addition to basic indices that indicate the importance of a paper such as number of views on search service and mentions on social media which based on user’s behavior related to papers on the Internet. Actually, using the search log of CiNii Articles for two years and the reference data on social media, we analyze the differences and characteristics of views and mentions to the same paper set and verify the validity of the proposed index.